SEGMENTASI PENGUNJUNG OBJEK WISATA PULAU CINTA TELUK JERING KABUPATEN KAMPAR - Selly Angriani; Andri Sulistyani (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2019)
Tourism object Pulau Cinta is one of the attractions in Kampar Regency and is worth to developing. The reason researchers chose this attraction is because the number of visits continues to increase every year. Based on the increase in visits, it is necessary to segment or group visitors according to needs, characteristics and the same relationship. Can be adapted to existing market segments. This study tries to describe the segmentation of visitors on Pulau Cinta, Teluk Jering, Kampar Regency. Segmentation used is geographical segmentation, demographic segmentation, and psychographic segmentation. The method used by the author is a quantitative descriptive method with a sample of 100 respondents. Data collection techniques used were observation, interviews, questionnaires or questionnaires. The results of the study of visitors who came to Pulau Cinta Teluk Jering were 92% received from Riau Province, 82% were received from outside Kampar Regency which came from Pekanbaru City community. The majority of visitors are women and are unmarried. With the age of around 15-25 years who dominate students with an average income of under 1 million. Large family visitors who have a core population of 5 people with an average monthly 1,000,000-2,000,000. Some facilities are used such as parking lots, photo spots, eating places, mosques, and others. Activities of visitors taking pictures and going around the tourist area. 65% of them visit friends and colleagues with a refreshing purpose. They know information through social media and 61% visit using motorbikes and through bad roads. Entrance rates are cheap and will be sent to Pulau Cinta Teluk Jering to visit. Keywords: Segmentation, Visitors, Teluk Jering.